Introduction of Research Master Students in the Problems of the Organization of Learning Activities in the Secondary School (Based on the Natural Sciences) - Guruzhapov V. A; Sanina S. P. (Moscow State University of Psychology and Education, 2015)
The article focuses on the designing of disciplines, based on the competence and activity approach to the content and methods of training of future teachers in the research psycho-pedagogical master's program. Particular attention is paid to the creation of problematic situations, in which research master students find themselves in the position of supervisors examining the educational activity. The authors provide examples of how students perform expert-analytical tasks based on analysis of training activities developed in the theory of developmental education by Davydov scholar school. There are samples of test items to assess how students have learned the content of the discipline, as well as to determine their ability and willingness to perform professional activities. These tasks were performed by master students as well as developing training teachers in elementary school and secondary school teachers. Testing the «Design and research of learning activities in the science lessons in secondary school» course allows us pre argue that psycho-pedagogical research master program allows to train future research training specialist using professional tasks related to expertise and design of training activities. Master students reach an acceptable level of competence for the performing the expert-analytical tasks. We propose to discuss if natural-scientific training of master students is one of the conditions for full cooperation between future research training specialist and teachers in order to improve the education of adolescents in the field of natural sciences